Features of Perception and Experience of Time in Children with Autism Spectrum Disorders by Case Description Materials - Polukarova I. O. (Psychological and Pedagogical Support of General, Special and Inclusive Education of Children and Adults, 2021)
The relevance of studying the experience of time in children with autism spectrum disorders is discussed on the example of two cases. The theoretical substantiation of this problem is given, as well as the complexity of studying this modality in children with autism spectrum disorder is considered. The reasons why it is necessary to study the problem of the experience of time in children with autism spectrum disorder are discussed. The experience of time in children with autism spectrum disorder is described on the basis of two cases.
Keywords: психолого-педагогическое сопровождение; расстройства аутистического спектра; переживание времени; восприятие времени; feelings of time; time perception; ASD; triangulation methodology